Syn-accretionary multistage assembly of an Early Jurassic Alaskan-type intrusion in the Canadian Cordillera: U-Pb and [.sup.40]Ar/[.sup.39]Ar geochronology of the Turnagain ultramafic-mafic intrusive complex, Yukon-Tanana terrane - Nixon, Graham T; Scheel, J. Erik; Scoates, James S; Friedman, Richard M; Wall, Corey J; Gabites, Janet; Jackson-Brown, Sarah (Canadian journal of earth sciences, 2020)
The magmatic evolution of the Early Jurassic Turnagain Alaskan-type intrusion is inextricably linked to terrane accretionary events at the North American continental margin. We have calibrated the multistage assembly of the Turnagain ultramafic-mafic complex using high-precision air and chemical abrasion ID-TIMS U-Pb and [.sup.40]Ar/[.sup.39]Ar geochronology. Our results are the first published geochronological calibration of zoning in an Alaskan-type intrusion. Three of four intrusive phases (Stages 1-4, oldest to youngest) were successfully dated. Cooling ages obtained on Stage 2 dunite-wehrlite include statistically identical [.sup.40]Ar/[.sup.39]Ar plateau dates of 187.4 [+ or -] 1.5 (2[sigma]) Ma on hornblende and 188.6 [+ or -] 1.2 Ma on phlogopite, and a concordant [.sup.206]Pb/[.sup.238]U date of 190.3 [+ or -] 4.6 Ma on titanite. Stage 3 diorite has a [.sup.206]Pb/[.sup.238]U zircon crystallization age of 188.11 [+ or -] 0.13 Ma. Stage 4 wehrlite and leucodiorite yield [.sup.206]Pb/[.sup.238]U zircon crystallization ages of 185.68 [+ or -] 0.19 and 185.30 [+ or -] 0.12 Ma, respectively. The ca. 189 Ma phlogopite date represents a minimum crystallization age for Stage 2, indicating that assembly of the Turnagain intrusion spanned at least ~4 million years from ca. 189 Ma to 185 Ma. Regional progressive contractional deformation in the Early Jurassic is constrained by the geochronological results (>189 to <185 Ma) and initially generated northeast-vergent folds in the country rocks (>189 Ma), deformed Stage 1 wehrlite-clinopyroxenite prior to emplacement of Stages 2-4, and subsequently thrust the intrusion and its host rocks onto the ancient North American continental margin (<185 Ma). Contrary to previous interpretations, new geophysical data support an allochthonous origin for the host rocks of the Turnagain intrusion. The Turnagain host succession is correlated with late Paleozoic arc-related and basinal lithostratigraphic units developed at the inboard margin of the accreted Yukon-Tanana terrane and peripheral to the Slide Mountain marginal ocean basin. The geochronological results rigorously constrain the timing and style of Early Jurassic deformation attending the initial accretion of allochthonous arc terranes in the northern Cordillera.